Hubungan Komunikasi Terapeutik Perawat pada Pelaksanaan Orientasi Pasien Baru dengan Kepuasan Pasien di RS TK.II Kartika Husada Pontianak - Fengki Suwito; Wiwin Priyantari (Jurnal Indonesia Sehat, 2022)
Background: The relationship of therapeutic communication is a communication by nurses to create trusting relationships and to planning an implementation that according to patient needs and to achieve patient satisfaction. The new patient orientation is a agreement between nurses and patients or families in providing nursing care. In this case, therapeutic communication plays an important role in increasing therapeutic relationship between nurses and clients with an expected outcome of satisfied clients. Client satisfaction is a vitally indispensable indicator to improve hospital services. Purpose: The aim of this research is to understand the nursing therapeutic communication on implementation of new natient orientations with patient satisfaction in RS Tk. II Kartika Husada Pontianak. Method: This research was used the Quantitatif which is using the Cross Sectional Approach. Total sampling were used in this research. The total respondent are 35 peoples. Analysis in this study used chi-square. Result: Obtained p value = 0,000 (p<0,05). means there are relationship between orientation of new patient with patient satisfaction. Conclusion: There is a Relationship of Nursing Therapeutic Communication on the Implementation of New Patient Orientation With Patient Satisfaction In RS Tk. II Kartika Husada Pontianak. Keyword: Therapeutic Communication , New Patient Orientation, Patient Satisfaction